(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, the authors define and explore the notion of an L-convex sublattice in an L-lattice. The investigations in this paper lead to ’The Unique Representation Theorem’ for L-convex sublattices. Also, the authors effectively use the concept of order reversing involution on the lattice L of truth values to define complement of an L-set. Further, they employ this notion in the studies of L- prime ideals and L-maximal ideals.